Membangun kepercayaan pelanggan dengan etika bisnis, kualitas layanan, dan manajemen risiko yang komprehensif - Lestari, Putri Ayu (Maliki Interdisciplinary Journal, 2024)
This research explores the sustainable relationship between business ethics, service quality, and efforts to build customer relationships through risk management. The research method used is literature analysis from related studies. The research results show that the application of business ethics can influence the quality of services provided by the organization, and can strengthen efforts to build relationships with customers. Good risk management can maintain the trust and loyalty of stakeholders towards the company, thereby helping to improve performance and long-term business success. Risk management must be carried out with appropriate business ethical principles, such as integrity, transparency, honesty, and social responsibility. Risk management in business ethics is not only about strengthening relationships with stakeholders but also about ensuring that the company operates ethically and responsibly in all aspects of its business.